Varying speed modulation of continuous-flow left ventricular assist device based on cardiovascular coupling numerical model. Issue 9 (11th August 2021) - Liu, Hongtao; Liu, Shuqin; Ma, Xiaoxu
Abstract: Continuous-flow left ventricular assist devices (CFLVADs) routinely operate at a constant speed for the support of a failing heart, which decreases the pulsatility in the arteries. Some late complications could be related to a long-term lack of pulsatility. Modulating the CFLVAD speed is a solution to enhance the pulsatility. The purpose of this study is to modulate multiple varying speed patterns and investigate their effects on the ventricle and vascular system. A cardiovascular coupling numerical model is developed to provide a simulation platform for testing the varying speed patterns. The varying speed patterns are modulated by combining the shape, amplitude, frequency, phase shift, and pulsatile duty cycle of the speed profile. The influence of varying speed support is examined by analyzing the indexes of pulsatility, indexes of ventricular unloading, and hemodynamic variables. The results show that the synchronous counterpulsation pattern can effectively reduce the ventricular unloading indexes, whereas the low-frequency asynchronous pattern can effectively increase the vascular pulsatility indexes. Also, the hemodynamics with synchronous varying speed support is more physiological than that with asynchronous varying speed support. This study provides valuable insight for further optimization of varying speed modulation by weighing vascular pulsatility, ventricular unloading, and hemodynamics.